2023
DOI: 10.2174/1389450124666230731094837
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and Cell Division: Potential Pharmacological Targets in Cancer Therapy

Abstract: Microtubules are a well-known target in cancer chemotherapy because of their critical role in cell division. Chromosome segregation during mitosis depends on the establishment of the mitotic spindle apparatus through microtubule dynamics. The disruption of microtubule dynamics through the stabilization or destabilization of microtubules results in the mitotic arrest of the cells. Microtubule-targeted drugs, which interfere with microtubule dynamics, inhibit the growth of cells at the mitotic phase and induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 225 publications
0
6
0
Order By: Relevance
“…Secondly, we found that BC patients had lower IC50 and greater drug molecule affinity for docetaxel, paclitaxel and vinblastine in the high KCNK1 expression group. The three drugs mentioned above were reported to work by blocking the progression of the cell cycle, which ultimately led to the death of the cancer cells [ 51 , 52 ]. Paclitaxel and docetaxel might affect the proliferation of BRCA cells by modulating potassium currents, and TME could induce docetaxel resistance [ 42 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we found that BC patients had lower IC50 and greater drug molecule affinity for docetaxel, paclitaxel and vinblastine in the high KCNK1 expression group. The three drugs mentioned above were reported to work by blocking the progression of the cell cycle, which ultimately led to the death of the cancer cells [ 51 , 52 ]. Paclitaxel and docetaxel might affect the proliferation of BRCA cells by modulating potassium currents, and TME could induce docetaxel resistance [ 42 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules play a vital role in the movement of chromosomes during cellular division. 35 As most tubulin destabilized agents disrupted the regulated cellular cycle distribution, flow cytometric analysis was performed to determine the impact of quinoline-4-methoxycinnamide hybrid 6e on the HepG2 cell cycle. The cancerous cells were treated with the tested compounds at 2.46 μM and control for 48 h. As illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 25 - 27 Hence, targeting microtubule (MT) dynamics to disrupt mitotic spindle assembly and reduce chromosomal separation and chromosomal instability (CIN) during mitosis in lung cancer cells has been widely employed as a therapeutic strategy using chemotherapy drugs in cancer treatment. 28 Previous research has demonstrated that during mitosis, Aurora A kinase facilitates microtubule (MT) nucleation around chromatin through the phosphorylation of NEDD1. This phosphorylation event promotes the proper assembly of a functional mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Paclitaxel, or docetaxel, which act on the microtubule paclitaxel site, cause mitosis arrest of cells by destroying the microtubule network, but it is also believed that paclitaxel exerts its anti-cancer effect by causing chromosomal malfusion on the multipolar spindle of cancer cells, increasing chromosomal instability. 28 , 40 Cisplatin plus pemetrexed, paclitaxel, or docetaxel is the first-line treatment of choice in driver-negative cases of advanced LUAD. Crizotinib is recommended for patients with positive ALK and ROS1 fusion genes, but unfortunately our results did not show a correlation between NEDD1 and other driver genes.…”
Section: Discussionmentioning
confidence: 99%